2014
DOI: 10.1111/jicd.12117
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of autologous platelet concentrates in treatment of intrabony defects: a systematic review and meta‐analysis

Abstract: The aim of the present review is to systematically evaluate the additive effect of autologous platelet concentrates (APCs) in treatment of intrabony defects when used along with other regenerative procedures and when used alone in terms of clinical and radiological outcomes. A search was performed in electronic databases (i.e., MEDLINE and the Cochrane Central Register of Controlled Trials) in order to identify randomized clinical trials (RCTs) assessing the additive efficacy of APCs for healing and regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
91
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 42 publications
5
91
1
7
Order By: Relevance
“…A recent systematic review and meta analysis on the usefulness of autologous platelet concentrates on intrabony defect management revealed that PRP has a significant additive effect when used along with bone grafts for regeneration of intrabony defects [14]. This study was carried out to compare the percentage of platelet enrichment achieved in three PRP preparation protocols suggested by different authors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta analysis on the usefulness of autologous platelet concentrates on intrabony defect management revealed that PRP has a significant additive effect when used along with bone grafts for regeneration of intrabony defects [14]. This study was carried out to compare the percentage of platelet enrichment achieved in three PRP preparation protocols suggested by different authors.…”
Section: Discussionmentioning
confidence: 99%
“…Since PRF does not contain anti-coagulants, it forms a fibrin clot within minutes after blood collection that has since been described and utilized as a three-dimensional scaffold for tissue regeneration [23,24,25]. Despite having complete immune-biocompatibility, other advantages include faster angiogenesis of tissues, which leads to faster wound healing [26,27,28,29]. For these reasons, the use of PRF has been widespread in oral surgery and continues to grow exponentially in use [30].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding TE in dentistry, the introduction of new membranes able to enhance guided tissue regeneration (GTR) in periodontology [32,33,34] and of autologous platelet concentrates (PRP and PRF) with membranes for guided restoration of bone loss in oral surgery, happened in 1980–1990 [35,36,37] and can be considered the beginning of the new techniques based on three principal elements of tissue engineering: stem cells, scaffolds, and signaling molecules [38]. …”
Section: Introductionmentioning
confidence: 99%